Systemic staphylococcosis in partridge chicks - Hadi Tavakkoli; Reza Kheirandish; Reza Ghanbarpoor; Zahra Mohseni (Eurasian Journal of Veterinary Sciences)
Aim: Staphylococcus infection is primarily caused by Staphylococcus aureus in poultry. Because little information was available in the literature about game birds experiencing staphylococcosis, this investigation was undertaken to evaluate the disease in partridge chicks. Materials and Methods: Systemic staphylococcosis was induced in 18 days old Alectoris chukar by intravenous injection of a suspension containing 106 cfu/mL of viable Staphylococcus aureus organisms. Results: Injection resulted in a fever response after 30-hours post-inoculation. The disease rapidly developed over the 48- hour period with potentially devastating consequences, including huddling, lethargy, ruffled feathers, decreased activity, unable to stand, wing droop, decreased feed and water consumption, growth depression and lameness. Gross and histopathological examination of internal organs revealed that the injuries originally occurred in the kidneys, liver, spleen, lungs, alimentary tract, pancreas, heart, brain, joints and tendons sheaths. Lesions of systemic staphylococcal infection in partridge chicks consist of necrosis, vascular congestion, thrombosis, abscess formation, arthritis, synovitis and marked heterophilic infiltration in affected organs. Conclusion: The diversity of clinical signs and lesions observed suggests the susceptibility of chukar partridge chicks to systemic staphylococcosis.